MicroRNA-145 in urologic tumors: biological roles, regulatory networks, and clinical translation - Gan, Lifeng; Li, Wei; Chen, Qi; Cheng, Le; Zhang, Fangtao; Zhong, Haidong; Lu, Yiran; Zheng, Liying; Qian, Biao (Frontiers in Pharmacology, 2025)
Tumors of the urinary system primarily encompass prostate, bladder, and kidney cancers, which exhibit high morbidity and mortality rates worldwide and pose a particularly significant threat to men’s health. Given the associated high morbidity and mortality, early diagnosis and effective treatment are crucial. Consequently, innovative research is urgently needed to enhance the clinical care of patients with urologic cancers. Recent studies have demonstrated that microRNAs (miRNAs), as key non-coding RNA molecules that regulate gene expression, play a vital regulatory role in malignant tumor development by binding to the mRNA 3′-UTR region. Large-scale genomic analyses (e.g., TCGA Pan-Cancer Atlas) reveal that over 50% of miRNA genes reside in cancer-associated regions, regulating >60% of protein-coding genes. miR-145 exemplifies this paradigm, with its dysregulation causally linked to tumor proliferation, metastasis, and therapy resistance. Among them, miR-145, as a regulatory molecule with significant anticancer properties, presents unique expression characteristics and functional mechanisms in urological tumours. In this review, we summarize the role of miR-145 in specific urological tumors, along with its downstream target molecules and cells, which may enhance our understanding of miR-145 in these cancers. In conclusion, miR-145 is a multifaceted regulator in urological oncology that has strong potential to range from non-invasive biomarker discovery to therapeutic strategies that work synergistically with conventional treatments, ultimately advancing precision medicine in prostate, bladder, and kidney cancers.